Afterword: Sincerity and Self-Similarity - Russett, Margaret (Christianity & literature, 2017)
The article offers the author's insights on romantic poetry which is synonymous to sincerity and self-similarity. Topics mentioned the aphorism concept of poet William Blake, his book "The Marriage of Heaven and Hell," and the poem "Tintern Abbey" by William Wordsworth. It also mentioned the literary history of sincerity offred by literary critic Lionel Trilling.